2021
DOI: 10.5344/ajev.2021.21007
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Improves Vine Physiology and Fruit Composition in Grapevine Red Blotch Virus-Infected Vitis vinifera L.

Abstract: for technical assistance related to data collection and laboratory work. The authors also thank Results Partners, LLC and Belle Fiore Estate and Winery for their assistance with field plot maintenance and provision of the study site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The Central Coast of California, a prominent region with several distinguished American Viticultural Areas (AVAs), is a Mediterranean-climate region stretching along the coast of California from San Francisco Bay to Santa Barbara County. Most vineyards on the Central Coast of California apply supplemental irrigation, intending to improve quality, yield, phenolic composition, and water efficiency [23,24]. Studies have shown that the timing of reduced deficit irrigation on grapes before and after véraison can increase phenolics and anthocyanins [12,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…The Central Coast of California, a prominent region with several distinguished American Viticultural Areas (AVAs), is a Mediterranean-climate region stretching along the coast of California from San Francisco Bay to Santa Barbara County. Most vineyards on the Central Coast of California apply supplemental irrigation, intending to improve quality, yield, phenolic composition, and water efficiency [23,24]. Studies have shown that the timing of reduced deficit irrigation on grapes before and after véraison can increase phenolics and anthocyanins [12,23,25].…”
Section: Introductionmentioning
confidence: 99%